The synthesis of automated control system of crops’ water supply at subsoil moistening - Lievi, L. I. (Scientific Progress & Innovations, 2019)
The purpose of the article is to substantiate the effective approach to the synthesis of the structural scheme of the cascade-combined automated system for controlling moisture supply of a module soil plot by changing the groundwater level. Research methods include models and methods of systemic-structural analysis and the principles of adaptive regulation of complex technical systems under uncertain conditions. The results of the research. The cascade-combined structural scheme of automated moisture regulation system for crops at subsoil moistening by changing the groundwater level has been developed. It has been shown that this system has two regulating circuits: the internal circuit for regulating water level in the master well of the cascade-combined automated moisture regulation system for a module plot of soil and the external setting circuit for regulating the suction pressure of the soil characterizing its humidity. The elements of scientific novelty. A two-circuit structural scheme of automated control system for moisture supply of crops in case of subsoil moistening with perturbations has been developed. Practical significance. This development was carried out to increase the efficiency of functioning automated systems for regulating moisture supply of crops during subsoil moistening and ensure the obtaining of guaranteed crop yields with simultaneous saving water and energy resources.